Scientists: Engage the Public! - Erika C. Shugart (American Society for Microbiology, 2015)
ABSTRACT Scientists must communicate about science with public audiences to promote an understanding of complex issues that we face in our technologically advanced society. Some scientists may be concerned about a social stigma or “Sagan effect” associated with participating in public communication. Recent research in the social sciences indicates that public communication by scientists is not a niche activity but is widely done and can be beneficial to a scientist's career. There are a variety of approaches that scientists can take to become active in science communication.